2022
DOI: 10.1109/access.2022.3202941
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimension Digital Twin Reference Architecture Model for Functionality, Dependability, and Life Cycle Development Across Industries

Abstract: The Digital Twin concept promises numerous applications across industries and its physical twin's entire life cycle. Although numerous architectures have been proposed to develop and describe the setup of Digital Twin applications, current Digital Twin architectures do not address the versatile crossindustry character of the Digital Twin concept, its safety, security, and privacy aspects, and are often use case-specific and inflexible. We propose a three-dimensional Digital Twin reference architecture model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Patents and papers without English abstracts were excluded. Meanwhile, the contents of papers are unrelated to healthcare for humanity and instead focus on production quality were excluded even though their keywords meet the requirements of this review, such as the paper reported by Newrzella et al 19 The review commenced in 2018 primarily because most general papers in the databases mentioned above were published during that year. Since 2018 can be regarded as the initial year for DT development, it was chosen as the starting point for the review.…”
Section: Methodsmentioning
confidence: 99%
“…Patents and papers without English abstracts were excluded. Meanwhile, the contents of papers are unrelated to healthcare for humanity and instead focus on production quality were excluded even though their keywords meet the requirements of this review, such as the paper reported by Newrzella et al 19 The review commenced in 2018 primarily because most general papers in the databases mentioned above were published during that year. Since 2018 can be regarded as the initial year for DT development, it was chosen as the starting point for the review.…”
Section: Methodsmentioning
confidence: 99%
“…Newrzella et al [34] compare various Digital Twin architectures in terms of their functionality. They derive the functional elements of the physical entity, integration element, data management and information element, modelling and simulation element and the decision and user interfacing element.…”
Section: It Infrastructures For Digital Twinsmentioning
confidence: 99%
“…The sensors and other modifications to the physical system must therefore be considered equally for the integration and asset layers. In some reference architectures (e.g., [32,34]), initial preprocessing of the data is also carried out in the same layer as the sensor system. In the context of this article, this is explicitly not conducted; all data processing in the various stages is carried out in the models in the functional layer in order to have everything in one place.…”
Section: Sensors and Other Modifications Of The Physical Twinmentioning
confidence: 99%
“…Digital Twin applications with different capabilities can be represented by the reference architecture model proposed in [31], where several state-of-the-art architectures and reference models are discussed and compared. This work shows that none of the existing solutions that involve the Digital Twin integration dimension proposes a well-defined framework to explicitly address the interoperability challenges.…”
Section: Related Workmentioning
confidence: 99%